Retorika Deliberatif pada Podcast Suara Berkelas #67: Narasi Mindset Perempuan - Atika Syalsabila Putri; Azhar (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
The rapid proliferation of digital audio-visual platforms has created new public spheres in which persuasive discourse about women's empowerment circulates at an unprecedented scale. This study examines the deliberative rhetorical strategies deployed in the women's mindset narrative presented in episode #67 of the Indonesian YouTube podcast Suara Berkelas, featuring guest speaker Lavina Sabila. Guided by Aristotle's tripartite model of persuasion ethos, pathos, and logos the study adopts a descriptive qualitative method with rhetorical analysis applied to the full 52-minute 29-second podcast transcript. Data were gathered through systematic observation and documentation, and analysed using Miles and Huberman's interactive model alongside triangulation of sources, techniques, and time. Findings reveal that ethos is established through Lavina's professional credibility as founder of Inong Carong and lived experiential wisdom; pathos operates through emotional resonance with gender stigma and personal vulnerability; and logos is constructed through rational arguments regarding financial independence and skill mastery as antidotes to fear. The coherent interplay of these three pillars constitutes effective deliberative rhetoric that orients female audiences toward transformative cognitive and behavioural change. This study fills a gap in scholarship on podcast rhetoric that has remained predominantly masculine in orientation.